2020
DOI: 10.1155/2020/1315202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Beneficial Effects of Hydroxytyrosol- and Oleuropein-Rich Olive Leaf Extracts on High-Fat Diet-Induced Lipid Metabolism Disturbance and Liver Injury in Rats

Abstract: Oleuropein and hydroxytyrosol, as major compounds of olive leaves, have been reported to exert numerous pharmacological properties, including anticancer, antidiabetic, and anti-inflammatory activities. The purpose of this study is to evaluate and compare the protective effect of oleuropein- and hydroxytyrosol-rich extracts, derived from olive leaves, on high-fat diet-induced lipid metabolism disturbance and liver injury in rats. In this respect, four groups of male rats (8 per group) were used: control group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
72
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 52 publications
8
72
2
Order By: Relevance
“…(2020) reported that olive leaf therapy exhibited hepatoprotective effects by decreasing ALT and AST levels due to its antioxidant properties (11). Although our findings are in agreement with the study by Fki et al, the decrease in ALT and AST levels was not significant in our treated diabetic rats (Fig.…”
Section: Effect Of Ole On Pain Responsesupporting
confidence: 91%
See 1 more Smart Citation
“…(2020) reported that olive leaf therapy exhibited hepatoprotective effects by decreasing ALT and AST levels due to its antioxidant properties (11). Although our findings are in agreement with the study by Fki et al, the decrease in ALT and AST levels was not significant in our treated diabetic rats (Fig.…”
Section: Effect Of Ole On Pain Responsesupporting
confidence: 91%
“…In the previous studies, oleuropein has been reported to be a peroxisome proliferator-activated receptor α (PPARα) ligand, and oleuropein treatment reduces in rat hepatocytes the activity of the rate(HMG-CoA) reductase (28,29). Moreover, it was reported that treatment with olive leaves significantly decreased serum cholesterol and triglyceride levels in rats fed a high fat diet(11). Similarly, we found that treatment with low-dose olive leaf extract significantly reduced serum total cholesterol (p < 0.01), but resulted in no significant improvement in triglyceride levels (Fig.…”
supporting
confidence: 71%
“…In our study, LPS challenge resulted in a 100% mortality rate at the seventh day, whereas, OLE pretreatment increased the survival rate to 66.3%. Oleuropein has been recorded to have valuable cardioprotective, antioxidant, 22,23 and anti-inflammatory effects. 24 Sepsis can induce disorders in many organs and lead to death.…”
Section: Discussionmentioning
confidence: 99%
“…Olive leaves constitute 10% of the raw material sent to oil mills, 7‐10 and are a source of antioxidant compounds with different uses and properties (i) as ingredients to obtain functional foods 11‐16 ; (ii) as natural preservatives, as substitutes for chemical ones, exploiting their antioxidant and antimicrobial effects to increase the shelf‐life of foods and then reduce the food lost; 13‐18 (iii) in the biomedical field with studies on genotoxicity, antinflammatory, anti‐carcinogenic, and other health‐related effects 19,20 …”
Section: Introductionmentioning
confidence: 99%